AZAS LUDIC DALAM KERAMAIAN BUNYI RITUS NGAROT - Aton Rustandi Mulyana (Institut Seni Indonesia Surakarta, 2011)
This paper questions the relationship between sound crowd and the principle of ludic that is present in a rite Ngarot, one of a series of rites farmers in Lelea Indramayu, West Java. Based on Homo Ludens by Johan Huizinga’thoughts and supported by its liminality by Victor Turner. many ludic nature shown through its playing principles, that is free, temporary, closed, tense, but at the same order. The nature of liminality is revealed through the presence of a celebrated rite ngarot sometime before the growing season in the early half of the rainy season, as well as celebrations carried on the threshold between the two events daily, or between an unusual event with a regular event. Key words : sound, ritual, ngarot, ludic, liminality.